Project To Strengthen the Profile of Pancasila Youth at Madrasah Aliyah Al Furqon Bugul Lor Panggungrejo Pasuruan - Mashuda (JURNAL ILMU PENDIDIKAN, 2024)
The project to strengthen the profile of Pancasila youth or P5 is an interdisciplinary learning that aims to observe and think about solutions to problems in the surrounding environment. Madrasah Aliyah Al Furqon Bugul Lor is also one of those who implement it, researchers who happen to practice teaching there are involved in every P5 project activity with the theme of entrepreneurship by utilizing surrounding ingredients which are local wisdom such as making a refreshing and healthy drink "turmeric star fruit wulu" , "moringa leaf powder", "making ecobricks", "making ice cream", application of P5 with a democracy theme through the election of the osim chairman, application of P5 with the theme of love for the country through commemoration of santri day, teacher's day and heroes' day, application of P5 with the theme mutual cooperation through clean Fridays, implementation of P5 with the theme of faith and devotion through congregational prayers, istghosah, and pilgrimages to auliya' graves. In principle, the implementation of P5 at Madrasah Aliyah Al Furqon involves all school components starting from the teaching board, students and female students. The effectiveness of implementing P5 at MA Al Furqon Bugul Lor is very interesting to carry out research so that it can be an example for other private schools.